Investigating EFL Undergraduate Learners' Preferred Input and Tasks for Extensive Listening in Digital Learning - Rizaldy Hanifa; Honesty Yonanda Ayudhia; Devy Kurnia Alamsyah; Andri Wardana; Siti Rahimah Yusra (English Department FBS UNP, 2025)
This study investigates university students' preferences regarding listening inputs and tasks in Extensive Listening (EL) activities within an English as a Foreign Language (EFL) context, emphasizing the impact of Information and Communication Technology (ICT) on language acquisition. The main objective was to identify engaging and effective English Language inputs and tasks that facilitate language comprehension. Data were collected from 217 EFL students in the English Language and Literature Department at a state university in West Sumatera using an online questionnaire consisting of 63 closed-ended items, which were analyzed through descriptive statistics. The findings indicate a preference among students for well-organized materials, a moderate speech rate, and exposure to various accents. Students found familiar topics and concrete information easier to comprehend; however, they valued the intellectual engagement provided by abstract or novel themes. Learners appreciated visual aids and acknowledged the cognitive advantages of audio-only exercises, highlighting the importance of a balanced approach in educational design. These insights indicate that educators ought to integrate explicit instruction with opportunities for independent learning by providing a range of listening materials suited to various comprehension levels. To improve engagement and learning outcomes, English Language activities must incorporate both familiar and innovative content, along with diverse linguistic elements that challenge and support the development of students' listening skills. This approach may cultivate a more dynamic, ICT-enhanced learning environment that effectively enhances EFL listening proficiency.